The Importance Of Land Development And Reuse And Future Task (Eurasian Journal of Engineering and Technology, 2026)
This article analyzes the current state and priority areas of land development and reuse in agriculture in Uzbekistan. In the study, the melioration state of irrigated lands, the level of salinity, and degradation indicators were assessed based on statistical and regulatory sources. The results showed that a significant part of the land is saline to varying degrees, which is a limiting factor in agricultural efficiency. It is justified that the priority strategy should be the restoration of the quality of existing lands and their return to economic circulation, rather than the expansion of new lands. The article emphasizes the need for institutional strength, digital monitoring, and the introduction of resource-saving technologies in sustainable land resource management.